2020
DOI: 10.1101/2020.12.14.422735
|View full text |Cite
Preprint
|
Sign up to set email alerts
|

The interaction of curiosity and reward on long-term memory in younger and older adults

Abstract: The study was conducted to examine the individual and joint effects of extrinsic motivation, manipulated via monetary reward, and curiosity, a form of intrinsic motivation, on long-term memory in the context of a trivia paradigm, in healthy younger and older adults. During the incidental encoding phase on Day 1, 60 younger and 53 older participants viewed high- and low-curiosity trivia as well as unrelated face stimuli. Half of the participants in each age group received financial rewards for correctly guessin… Show more

Help me understand this report
View published versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

1
3
1

Year Published

2022
2022
2022
2022

Publication Types

Select...
3

Relationship

0
3

Authors

Journals

citations
Cited by 3 publications
(5 citation statements)
references
References 68 publications
1
3
1
Order By: Relevance
“…In contrast to the previous studies manipulating monetary reward within the trivia question paradigm (Murayama & Kuhbandner, 2011; Swirsky et al, 2021), we did not find a significant interaction between curiosity and incentive on any of our main measures of interest (recognition, high confidence recognition, cued recall). While the non-significant interaction effect may be explained by the differences in the design (e.g., materials, memory measures, and procedure to manipulate incentives compared to rewards), we also found an interesting dissociation between the effect of curiosity and that of incentives on memory.…”
Section: Discussioncontrasting
confidence: 99%
See 2 more Smart Citations
“…In contrast to the previous studies manipulating monetary reward within the trivia question paradigm (Murayama & Kuhbandner, 2011; Swirsky et al, 2021), we did not find a significant interaction between curiosity and incentive on any of our main measures of interest (recognition, high confidence recognition, cued recall). While the non-significant interaction effect may be explained by the differences in the design (e.g., materials, memory measures, and procedure to manipulate incentives compared to rewards), we also found an interesting dissociation between the effect of curiosity and that of incentives on memory.…”
Section: Discussioncontrasting
confidence: 99%
“…Jepma et al, 2012). The same curiosity effects have also been found in incidental encoding paradigms after short (Brod & Breitwieser, 2019; Galli et al, 2018; Gruber et al, 2014; Jepma et al, 2012; Ligneul et al, 2018; Mullaney et al, 2014; Murphy, Dehmelt, et al, 2021; Poh et al, 2021; Stare et al, 2018) and long (Fastrich et al, 2018; Gruber et al, 2014; Kang et al, 2009; Marvin & Shohamy, 2016; Murayama & Kuhbandner, 2011; Stare et al, 2018; Swirsky et al, 2021) delays between encoding and retrieval. Interestingly, incidental information that is semantically unrelated to the cue eliciting the feeling of curiosity but presented in close temporal proximity (i.e., during a state of high compared to low curiosity) is also preferably encoded (Galli et al, 2018; Gruber et al, 2014; Murphy, Dehmelt, et al, 2021; Stare et al, 2018).…”
Section: Introductionsupporting
confidence: 68%
See 1 more Smart Citation
“…Gruber et al, 2016; Murty & Adcock, 2014). The effects of curiosity on encoding, on the other hand, have consistently been found after short (Brod & Breitwieser, 2019; Galli et al, 2018; Gruber et al, 2014; Jepma et al, 2012; Ligneul et al, 2018; Mullaney et al, 2014; Murphy, Dehmelt, et al, 2021; Poh et al, 2021) and long (Duan et al, 2020; Fastrich et al, 2018; Gruber et al, 2014; Halamish et al, 2019; Kang et al, 2009; Marvin & Shohamy, 2016; Murayama & Kuhbandner, 2011; Swirsky et al, 2021) delays between encoding and retrieval. A study examining the effects of curiosity levels on later memory by testing half of the items after a short and the other half of the items after a long delay found that curiosity correlated with encoding at both time intervals (McGillivray et al, 2015).…”
Section: Monetary Incentives and Memory Consolidationmentioning
confidence: 96%
“…To be able to investigate incidental encoding (similar to previous research 38,65 ), participants were presented with a cover story that the study investigates problem solving, social cognition, and the associated brain processes. They were briefed that they would be performing a viewing and judgement task involving magic tricks inside the MRI scanner and that there would be an online follow-up assessment related to their responses a week later.…”
Section: Methodsmentioning
confidence: 99%